Scavenger receptors: key players in the immunological puzzle of lupus - Hahn, Sabine; Chitre, Monika; Shepard, Dominique; Rashid, Romana; Ramirez-Ortiz, Zaida G. (Frontiers in Lupus, 2025)
Scavenger receptors (SRs) play an important role in the innate immune response by recognizing and binding a variety of ligands to initiate the removal of both altered self- and non-self-antigens. Over the last two decades, SRs have become a forefront for their role influencing and contributing to inflammatory disease pathways. The findings discussed in this review show that the immunological role SRs play is (1) found in multiple organ systems and not limited to one disease or subset of symptoms; (2) part of both the innate and adaptive immune response in addition to influencing inflammatory signaling via non-immune cell subtypes; (3) both pro- or anti-inflammatory depending on which SR class or cell signaling pathway is being observed; (4) potentially useful for the development of therapeutics and diagnostic or prognostic biomarkers for autoimmune disease pathology. Understanding the role of SRs in the context of inflammation and autoimmunity will shed some light on the comprehension of heterogeneous diseases, such as Systemic Lupus Erythematosus.